Curriculum planning and evaluation: fundamental elements in the educational process (Dissertare, 2020)
The purpose of this research is to interpret the meanings attributed by the teachers of an Educational Unit in Ecuador to the curricular planning and evaluation processes, within the framework of their academic practice. The investigative value of the work rests on the need to emphasize the use of evaluation techniques and instruments in curricular planning, as the basis of an educational process supported by the ministerial guidelines of the MINEDUC-201600020A Agreement. The study is framed in the qualitative approach, under the phenomenological-hermeneutical method, with field design. To obtain the information, the semi-structured interview was used, applied to three key informants, teachers of the studied institution, with the support of the respective script. The analysis and interpretation of the information was carried out through the categorization by hermeneutical units, which allowed deriving emerging categories, which were later integrated into macro-categories. The findings reveal that teachers recognize curricular planning as a formal, systematized structure that focuses on the needs of students and requires teacher training for the application of strategies adapted to educational and ministerial demands; the predominant evaluation techniques are group to promote values. The final reflections emphasize that curricular planning serves as the basis for building learning experiences in accordance with the proposed objectives, to which evaluation techniques and instruments must be adapted. Finally, it is considered important to stress the importance of recognizing the educational quality standards of the country, as a basis for planning and curriculum evaluation.
Keywords: curricular planning; educational praxis; evaluation techniques and instruments; curriculum